Recurrent intraoperative silent ST depression responding to phenylephrine - P M Singh; Dipal Shah; Anjan Trikha (Wolters Kluwer Medknow Publications, 2012)
Intraoperative myocardial ischemia is attributed to decreased myocardial oxygen supply. We present an unusual case of recurrent, symptomless inferior wall ischemia in an apparently healthy male with no history of coronary artery disease after a spinal block. The recurring episodes were linked to tachycardia and presented with significant ST depression in Lead II with reciprocal elevation in lead aVL. The episodes responded to phenylephrine and subsided without residual sequelae.